2005
DOI: 10.1038/sj.gene.6364214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of malaria susceptibility determinants in the IFNG/IL26/IL22 genomic region

Abstract: Interferon-gamma, encoded by IFNG, is a key immunological mediator that is believed to play both a protective and a pathological role in malaria. Here, we investigate the relationship between IFNG variation and susceptibility to malaria. We began by analysing West African and European haplotype structure and patterns of linkage disequilibrium across a 100 kb genomic region encompassing IFNG and its immediate neighbours IL22 and IL26. A large case-control study of severe malaria in a West Africa population iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
(34 reference statements)
1
30
0
Order By: Relevance
“…Likewise, the Th2 subset aids in generating optimal antibody responses against plasmodium infections in humans and mice [32,37,38]. Th17 [39,40], Th22 [41], Tr27 [42], Tregs [43,44 ] and Tfh [45] have all been implicated in control of blood stage malaria. However, the contribution of none of these subsets has been as controversial as that of Tregs in malaria.…”
Section: Blood Stage Malaria: When Cd4 T Cells Call the Playmentioning
confidence: 98%
“…Likewise, the Th2 subset aids in generating optimal antibody responses against plasmodium infections in humans and mice [32,37,38]. Th17 [39,40], Th22 [41], Tr27 [42], Tregs [43,44 ] and Tfh [45] have all been implicated in control of blood stage malaria. However, the contribution of none of these subsets has been as controversial as that of Tregs in malaria.…”
Section: Blood Stage Malaria: When Cd4 T Cells Call the Playmentioning
confidence: 98%
“…The most common of these disease sequelae, severe malarial anemia (SMA), is responsible for the majority of the malariaassociated mortality in western Kenya (7,32,54). Based on historical presence of the disease, malaria has exerted a large impact on the human genome such that potentially harmful variants are preserved, largely because of the advantage offered in heterozygous individuals that are often protected from severe, complicated, and fatal malaria (14,19,21). Studies in our laboratory focused on variations in key cytokine genes have demonstrated associations between polymorphisms and SMA (4,37,38).…”
mentioning
confidence: 99%
“…Several polymorphisms (SNPs and microsatellite repeat) from the promoter, introns and UTR region of the IFNG gene have been reported (Koch et al, 2005). Some of these polymorphisms have been associated with diseases other than malaria in different world populations (Ding et al, 2008;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 98%